2010 IEEE 16th International on-Line Testing Symposium 2010
DOI: 10.1109/iolts.2010.5560238
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of NBTI induced delay

Abstract: Negative Bias Temperature Instability (NBTI) has become a major reliability concern for nanoscaled PMOS transistors. NBTI is a thermally activated process and its aftereffects (e.g. threshold voltage shift, current degradation and delay increment) increase exponentially with the rise in temperature. This paper presents a model of temperature impact on NBTI induced delay for PMOS transistor. It demonstrates the model on 90nm, 65nm and 45nm Predictive Technology Model (PTM) designs operating at temperature range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The deep dependency of NBTI to temperature is because the diffusion sub-processes of R-D modeling framework in oxide layer follow Fick's law, (e.g., hydrogen diffusion rate (D H ) decreases linearly with decreasing H density from Si-SiO 2 interface) and temperature variation exponentially affects the diffusion rate based on Arrhenius relation, which can be written as [9]:…”
Section: B Temperature Dependence Of Nbtimentioning
confidence: 99%
“…The deep dependency of NBTI to temperature is because the diffusion sub-processes of R-D modeling framework in oxide layer follow Fick's law, (e.g., hydrogen diffusion rate (D H ) decreases linearly with decreasing H density from Si-SiO 2 interface) and temperature variation exponentially affects the diffusion rate based on Arrhenius relation, which can be written as [9]:…”
Section: B Temperature Dependence Of Nbtimentioning
confidence: 99%
“…BTI induced ∆V th of each MOS transistor has its contribution to the additional gate delay [13]. A generalized formula that relate BTI induced ∆V th in a transistor to the additional delay is given by [10]:…”
Section: A Gate Delay Modelmentioning
confidence: 99%
“…In recent years, there is an escalation of interest in BTI analysis at the gate level [10][11][12][13][14][15]. Paul et al in [10] pioneered the work by performing NBTI analysis for the continuous inputs that resulted in the worst degradation and Haldun et al in [11] carried out the analysis for a modified model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher temperature can accelerate the generation of interface traps and thus exacerbates performance degradation. In [5], the authors showed that threshold voltage shift can increase up to 42% at high temperature. In addition to stress probability and temperature, supply voltage is also a major factor contributing to NBTI degradation.…”
Section: Introductionmentioning
confidence: 99%